PELANGGARAN HAM BERAT DAN TANGGUNG JAWAB NEGARA DALAM PENEGAKAN HUKUM INTERNASIONAL - Gettari, Trie Rahmi; Faisal, Muhammad (Ensiklopedia of Journal, 2025)
Abstract: Gross human rights violations, such as genocide, crimes against humanity, and war crimes, constitute serious challenges in international law. States have an obligation to prevent, punish, and provide reparations to victims of gross human rights violations in accordance with international legal instruments such as the Geneva Conventions and the Rome Statute. However, challenges such as impunity for state officials, the limitations of the International Criminal Court (ICC) jurisdiction, and international political influence hinder the enforcement of justice. This study uses a qualitative descriptive method to analyze the state's efforts in fulfilling its responsibilities related to gross human rights violations. The results show that despite the continued development of international efforts, significant obstacles remain, including political protection of perpetrators and the limitations of the ICC's jurisdiction. Therefore, increased international cooperation is needed to ensure justice for victims and accountability for perpetrators of gross human rights violations.Keywords: Gross human rights violations, State responsibility, International Criminal Court.